2019
DOI: 10.3389/fimmu.2019.01914
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial but Not Fungal Gut Microbiota Alterations Are Associated With Common Variable Immunodeficiency (CVID) Phenotype

Abstract: Common Variable Immunodeficiency (CVID) is the most frequent symptomatic immune disorder characterized by reduced serum immunoglobulins. Patients often suffer from infectious and serious non-infectious complications which impact their life tremendously. The monogenic cause has been revealed in a minority of patients so far, indicating the role of multiple genes and environmental factors in CVID etiology. Using 16S and ITS rRNA amplicon sequencing, we analyzed the bacterial and fungal gut microbiota, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 72 publications
(102 reference statements)
7
39
1
1
Order By: Relevance
“…Also, CVID patients in general had a lower alpha diversity than healthy controls (21). This was also observed by Fiedorova et al (25). In our study, a significant difference in alpha diversity could be shown between CVID patients and healthy donors as well as between CVID patients with non-infectious diarrhoea and those without diarrhoea.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, CVID patients in general had a lower alpha diversity than healthy controls (21). This was also observed by Fiedorova et al (25). In our study, a significant difference in alpha diversity could be shown between CVID patients and healthy donors as well as between CVID patients with non-infectious diarrhoea and those without diarrhoea.…”
Section: Discussionsupporting
confidence: 89%
“…So far, only few investigations of the CVID microbiome have been published (21)(22)(23)(24)(25)(26). The diversity of microbiota within one individual or its sample (alpha diversity) and the differences in distribution of different microbiota among samples or individuals (beta diversity) can be described.…”
Section: Introductionmentioning
confidence: 99%
“…Non-infectious complications of CVID are mainly caused by immune dysregulation. This chronic and aberrant systemic immune activation seems to be, at least in part, a consequence of increased microbial translocation [ 61 , 124 , 125 ]. Jørgensen et al investigated gut microbiota composition in 44 CVID patients, 45 patients with IBD and 263 healthy controls [ 126 ].…”
Section: Gut Microbiota–host Interactions In Human Inborn Errors Omentioning
confidence: 99%
“…Other reported conditions associated with an increased number of IELs include Hashimoto thyroiditis, Graves' disease, rheumatoid arthritis, psoriasis, multiple sclerosis, and systemic lupus erythematosus. Common variable immune deficiency also causes intestinal mucosal damage due to inflammation and/or infections [36]. Furthermore, chronic inflammatory bowel diseases and collagenous and lymphocytic colitis have been concurrently associated with proximal small intestinal intraepithelial lymphocytosis.…”
Section: Statement 1 a Methodological Approach To Duodenal Biopsy Amentioning
confidence: 99%